142 Effects of Truncating Variants in Titin on Cardiac Phenotype and Left Ventricular Remodelling in Dilated Cardiomyopathy. (3rd June 2016) - Tayal, Upasana; Buchan, Rachel J; Whiffin, Nicola; Newsome, Simon; Mazzarotto, Francesco; Walsh, Roddy; Ware, James S; Prasad, Sanjay; Cook, Stuart
Abstract : Background: The clinical course of dilated cardiomyopathy (DCM) is variable: while 20% of patients die within 5 years of diagnosis, up to 15% recover fully. DNA variants that truncate the sarcomeric protein titin (TTNtv) are found in up to 20% of DCM. We sought to characterise the phenotype of TTNtv DCM and evaluate the effect of TTNtv on left ventricular remodelling in DCM. Methods: 661 prospectively recruited DCM patients underwent targeted sequencing of TTN and cardiac MRI (CMR) scanning to evaluate left and right ventricular volumes, function, wall thickness and mass (Siemens scanners, 1.5T). TTNtv in constitutive exons were confirmed by Sanger sequencing or visual inspection of reads on IGV. Quantitative phenotypes were compared using t-tests or Mann-Whitney U tests as appropriate. A subgroup of 122 patients underwent follow up CMR scanning. Linear regression analysis was used to determine the effects of TTNtv on interval change in left ventricular ejection fraction (LVEF), left ventricular volumes and mass. Results: Targeted sequencing of 661 patients with DCM (mean age 57.3 years, 68% male) identified 62 patients (9.4%) with confirmed truncating variants in TTN (A band, n = 48; I band, n = 11; M band, n = 3). There was no difference in age at diagnosis between patients with and without TTNtv (54.1 yrs vs 57.7 yrs, p = 0.05). Patients with TTNtv had lower maximum and mean left ventricular wall thickness and lower indexed left ventricular stroke volume and mass (Table 1). There was no difference in baseline left or right ventricular ejection fraction between patients with and without TTNtv. 122 DCM patients (mean age 54.3 years, 66% male) underwent an additional CMR with a median follow-up interval of 2.6 years (IQR 1.4–4.6 years). Amongst these, 21 patients (16.9%) had TTNtv in constitutive exons (A band, n = 17; I band, n = 3; M band, n = 1). 67% of patients with TTNtv (14/21) showed an improvement in LVEF >5% compared to 50% of patients without TTNtv (51/101). The mean interval improvement in LVEF between baseline and follow up studies was 6.2% in patients with TTNtv compared to 4.6% in those without (p = 0.55). In regression analysis, the presence of a truncating variant in TTN was not predictive of the interval change in LVEF, indexed left ventricular end diastolic volume, end systolic volume, stroke volume and mass (Table 2). Conclusion: These data show that TTNtv DCM is phenotypically characterised by thinner left ventricular walls, lower left ventricular mass and indexed stroke volume in the absence of overt differences in ejection fraction or age at diagnosis. Notably, these data show that there is no evidence that DCM patients with TTNtv have a different pattern of left ventricular remodelling compared to patients without TTNtv. This implies that the presence of a titin truncating mutation in a patient with DCM does not preclude the possibility of functional recovery.